Arctic and Antarctic Sea Ice Mean State in the Community Earth System Model Version 2 and the Influence of Atmospheric Chemistry. Issue 8 (23rd August 2020) - DuVivier, Alice K.; Holland, Marika M.; Kay, Jennifer E.; Tilmes, Simone; Gettelman, Andrew; Bailey, David A.
Abstract: Arctic and Antarctic sea ice has undergone significant and rapid change with the changing climate. Here, we present preindustrial and historical results from the newly released Community Earth System Model Version 2 (CESM2) to assess the Arctic and Antarctic sea ice. Two configurations of the CESM2 are available that differ only in their atmospheric model top and the inclusion of comprehensive atmospheric chemistry, including prognostic aerosols. The CESM2 configuration with comprehensive atmospheric chemistry has significantly thicker Arctic sea ice year‐round and better captures decreasing trends in sea ice extent and volume over the satellite period. In the Antarctic, both CESM configurations have similar mean state ice extent and volume, but the ice extent trends are opposite to satellite observations. We find that differences in the Arctic sea ice between CESM2 configurations are the result of differences in liquid clouds. Over the Arctic, the CESM2 configuration without prognostic aerosol formation has fewer aerosols to form cloud condensation nuclei, leading to thinner liquid clouds. As a result, the sea ice receives much more shortwave radiation early in the melt season, driving a stronger ice albedo feedback and leading to additional sea ice loss and significantly thinner ice year‐round. The aerosols necessary for the Arctic liquid cloud formation are produced from different precursor emissions and transported to the Arctic. Thus, the main reason sea ice differs in the Arctic is the transport of cloud‐impacting aerosols into the region, while the Antarctic remains relatively pristine from extrapolar aerosol transport. Plain Language Summary: Arctic and Antarctic sea ice has undergone significant and rapid change with the changing climate. Here we assess Arctic and Antarctic sea ice in a new state‐of‐the‐art Earth System Model, the Community Earth System Model Version 2 (CESM2). In particular, we explore how the atmosphere impacts the sea ice. When the CESM2 model does not include chemistry of particles in the atmosphere, we find that Arctic clouds are thinner, which allows more sunlight to reach the sea ice at the surface in the spring and summer. As a result, the sea ice melts more so that it covers less of the Arctic Ocean surface and is overall thinner than in CESM2 simulations that do include chemistry of particles. In contrast, inclusion or lack of particle chemistry does not lead to large differences in the Antarctic sea ice thickness or surface area covered by sea ice. The reason for the opposite results in the hemispheres is that the particles that impact clouds are produced outside the Arctic and Antarctic. These particles are transported successfully to the Arctic, but the Antarctic remains relatively pristine from external particle transport. Key Points: Simulated sea ice matches Arctic and Antarctic observed mean extent and volume, and Arctic observed historic trends The Arctic sea ice state differs significantly in two model configurations from cloud‐aerosol chemistry impacts on surface radiation Seasonality of Arctic liquid clouds drives differences in the ice albedo feedback and the amount of summer ice loss